PENDEKATAN MA‘ĀNĪ AL-ḤADĪṠ TENTANG PERMINTAAN HIDUP MISKIN - Moh. Affan; Ahmad Syauqi Alaika Rohman (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This article examines the hadith concerning the request to live in poverty through the Ma‘ānī al-Ḥadīth approach, a method of hadith understanding that emphasizes the analysis of the meanings of lafaz, the historical context, and the moral objectives contained in the text. A hadith that literally appears as an encouragement to ask for a life of poverty is often misunderstood and creates debate among Muslim communities. This study employs a qualitative method with a library-research design, drawing sources from the Qur’an, primary hadith collections, classical commentaries such as those of al-Nawawī and Ibn Ḥajar, as well as contemporary literature including the works of Yūsuf al-Qaraḍāwī and various academic studies. The analysis shows that the request to live in poverty is not a normative command of the Prophet, but an expression of humility, simplicity, and inner freedom from dependence on worldly matters. A proper understanding of the hadith requires integrating linguistic analysis, comprehension of the socio-historical context, and the relevance of its values in modern life. This study affirms that Islam does not promote extreme asceticism or the romanticization of poverty; rather, it encourages a balance between spiritual piety and economic independence. The Ma‘ānī al-Ḥadīth approach proves effective in presenting a more proportional interpretation aligned with the guidance of maqāṣid al-sharī‘ah, enabling this research to contribute to scholarly discourse on hadith understanding and socio-economic ethics in Islam.